Good Governance: Patterns of Rice Distribution in Improving Commerce through the Role of the Economic Assembly of Muhammadiyah Association of Sidenreng Rappang Regency - Razak, Muhammad Rais Rahmat; Hakzah, Hakzah; Mursalat, Aksal; Thamrin, Nining Triani; AR, Trisnawaty (Hasanuddin University, 2024)
Rice is the main staple food in Indonesia, and Sidenreng Rappang District contributes significantly to rice production in South Sulawesi Province. However, rice distribution in this area faces significant challenges, including long marketing channels and high marketing margins, which disadvantage farmers. The Muhammadiyah United Economic Assembly plays an important role in optimizing distribution channels, providing access to financing to farmers, and facilitating cooperation between farmers and marketing institutions. This research used observation, interview, and documentation methods, with primary and secondary data. The results showed that the marketing margin of rice in Sidenreng Rappang District reached IDR 23,650/kg, with the largest profits enjoyed by wholesalers and retailers. Improving more efficient distribution channels can reduce marketing margins and improve farmers' welfare. Therefore, the role of the Economic Assembly of Muhammadiyah Association is crucial in creating a more efficient trade system and improving the economic welfare of the people in Sidenreng Rappang District.